Hypoxia impairs decitabine-induced expression of HLA-DR in acute myeloid leukaemia cell lines - Sam Humphries; Sean M. Burnard; Courtney D. Eggins; Simon Keely; Danielle R. Bond; Heather J. Lee (Clinical Epigenetics)
Abstract Background Hypomethylating agents (HMA), such as azacytidine (AZA) and decitabine (DAC), are epigenetic therapies used to treat some patients with acute myeloid leukaemia (AML) and myelodysplastic syndrome. HMAs act in a replication-dependent manner to remove DNA methylation from the genome. However, AML cells targeted by HMA therapy are often quiescent within the bone marrow, where oxygen levels are low. In this study, we investigate the effects of hypoxia on HMA responses in AML cells. Results AML cell lines (MOLM-13, MV-4-11, HL-60) were treated with DAC (100 nM) or AZA (500–2000 nM) in normoxic (21% O2) and hypoxic (1% O2) conditions. Hypoxia significantly reduced AML cell growth across all cell lines, with no additional effects observed upon HMA treatment. Hypoxia had no impact on the extent of DNA hypomethylation induced by DAC treatment, but limited AZA-induced loss of methylation from the genome. Transcriptional responses to HMA treatment were also altered, with HMAs failing to up-regulate antigen presentation pathways in hypoxia. In particular, cell surface expression of the MHC class II receptor, HLA-DR, was increased by DAC treatment in normoxia, but not hypoxia. Conclusion Our results suggest that HMA-induced antigen presentation may be impaired by hypoxia. This study highlights the need to consider microenvironmental factors when designing co-treatment strategies to improve HMA therapeutic efficacy.